Comparative field study of spring and summer leaf gas exchange and photobiology of the mediterranean trees Quercus ilex and Phillyrea latifolia - Penuelas, J.; Filella, I.; Llusia, J.; Siscart, D.; Piñol, J. (Journal of Experimental Botany, 1998)
Summer-induced changes in gas exchange, fluorescence and reflectance were measured on leaves of two co-occurring Mediterranean small trees, Quercus ilex and Phillyrea latifolia, in May, June and July 1996 in Central Catalonia (NE Spain). The humid 1996 summer only produced mild water stress conditions. However, photosynthesis (A) and stomatal conductance (gs) decreased in June and July in both species. In June P. latifolia had higher net photosynthetic rates and lower stomatal conductances than Q. ilex, thus exhibiting higher instantaneous plant water use efficiencies. In agreement with these results, the photo-chemical reflectance index (PRI, calculated as (R570-R531)/(R531+R570)) of P. latifolia was lower, suggesting a possible lower xanthophyll de-epoxidation state. However, P. latifolia had lower ΔF/F′ and therefore a lower electron transport rate (ETR). The behaviour of PRI confirmed previous studies indicating a strong relationship between PRI, ΔF/F′ , and photosynthetic radiation-use efficiency (PRUE). PRI offers a simple, portable means of assessing PRUE with the potential for remote sensing applications. Finally, the possible ecological consequences of these results on the behaviour of the two species studied under the predicted warmer and drier conditions of global change are discussed.
10.1093/jxb/49.319.22910.1093/jxb/49.319.229
Keywords: fluorescence; intrinsic water use efficiency; net photosynthetic rates; phillyrea latifolia; photochemical efficiency; photochemical reflectance index; photosynthetic radiation-use-efficiency; Quercus ilex; reflectance; Stomatal conductance; summer; water index